2004
DOI: 10.1097/00007632-200406010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of the Thoracic Vertebral Pedicle in an Indian Population

Abstract: These results suggest that even a 4-mm screw should be used carefully at the midthoracic level; 5-mm screw seems to be safe at upper and lower thoracic spine. Because of very small sagittal and transverse angle at mid and lower thoracic levels, the pedicular screw should be inserted along almost perpendicular line in these planes; 25-mm and 30-mm screw length appears to be safe at upper thoracic and lower thoracic levels, respectively. Pedicle entrance point lies along the midtrans-verse line at upper thoracic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
55
6
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 17 publications
25
55
6
1
Order By: Relevance
“…Ludwig's study indicated that using a 3.5 mm diameter screw and if 4.5 mm was used as a cut-off for attempting screw insertion, only 2% of the screws inserted would be likely to result in harm. The results concurred with clinical recommendations defining cut-offs of 4.0-4.5 mm using 3.5 mm screws at C3-7 [7,12,16,56], and 5 mm for pedicle screws in T1 [54]. At all with our current results following fluoroscopically assisted manual insertion of 3.5 mm diameter ATPS, safe placement is assumed at the C6 to T1-levels with pedicles showing an OPW of C5 mm.…”
Section: Risk Factors For Pedicle Perforationssupporting
confidence: 90%
See 1 more Smart Citation
“…Ludwig's study indicated that using a 3.5 mm diameter screw and if 4.5 mm was used as a cut-off for attempting screw insertion, only 2% of the screws inserted would be likely to result in harm. The results concurred with clinical recommendations defining cut-offs of 4.0-4.5 mm using 3.5 mm screws at C3-7 [7,12,16,56], and 5 mm for pedicle screws in T1 [54]. At all with our current results following fluoroscopically assisted manual insertion of 3.5 mm diameter ATPS, safe placement is assumed at the C6 to T1-levels with pedicles showing an OPW of C5 mm.…”
Section: Risk Factors For Pedicle Perforationssupporting
confidence: 90%
“…The current study confirmed that the cervical pedicle dimensions tend to increase in size from C3 to T1 [21], and that the pedicle transverse diameter (OPW) is the main determinant of critical pedicle perforations and of the maximum screw sizes to be used [6,54,55] with increasing accuracy of pedicle screw insertions at the caudad levels C6 to T1 [7,10,11,15]. In a study of Karaikovic et al [6] using the funnel technique, critical perforations occurred in 10.5% at C5, 5.3% at C6, and 0% at C7, which were 13.0% at C5 in the current series, but 0% at C6 to T1.…”
Section: Risk Factors For Pedicle Perforationssupporting
confidence: 77%
“…The morphometric profile of the thoracic pedicles in our study is comparable to figures quoted in other Asian anatomical studies [5,19]. We do not routinely perform computed tomography of thoracic pedicles prior to insertion of the pedicle screws.…”
Section: Discussionsupporting
confidence: 86%
“…The aim of this study was to assess the pedicle anatomy in a Chinese population based on CT scans. Previous studies had shown significant interracial differences of thoracic pedicle morphometry [2,4,10]. Therefore, a complete morphometry database of the thoracic pedicle is needed to determine the safety margin of transpedicular fixation in our population.…”
Section: Introductionmentioning
confidence: 99%